Simulation design of Photonic Crystal Fiber Temperature sensor based on Surface Plasmon Resonance - Namaa Salem Rahim,; Soudad S. Ahmed, (Iraqi Journal of Laser, 2024)
Photonic crystal fiber (PCF) sensors based on surface Plasmon resonance with a gold layer coating are prepared and studied in this paper for detecting environmental temperature. A finite element method is utilized to increase the critical geometry parameter. An air hole on the right side of the PCF core is covered utilizing a gold metal that has a thickness of 50nm. PCF cores with circular air holes coated in gold and filled with water samples had considerable confinement losses in the y-polarization direction. When the temperature rises from 48 °C to 75 °C the RI of water will reduce. Numerical analysis of the suggested sensor was conducted utilizing FEM. Simulation using the COMSOL software was used to estimate performance parameters such as amplitude sensitivity, wavelength sensitivity, and resolution. Results indicate that the air hole covered with (Au) acts as a (SPR) sensing feed to sense the RI of water. In the sensing range (1.32-1.3266), amplitude sensitivity SA was 422.154RIU−1 and maximum resolution was 2.75∗10−5 RIU.